An In Vivo Stable Isotope Labeling Method to Investigate Individual Matrix Protein Synthesis, Ribosomal Biogenesis, and Cellular Proliferation in Murine Articular Cartilage. Issue 2 (25th February 2022) - Kobak, Kamil A; Batushansky, Albert; Borowik, Agnieszka K; Lopes, Erika Prado Barboza; Peelor III, Frederick F; Donovan, Elise L; Kinter, Michael T; Miller, Benjamin F; Griffin, Timothy M
Abstract: Targeting chondrocyte dynamics is a strategy for slowing osteoarthritis progression during aging. We describe a stable-isotope method using in vivo deuterium oxide labeling and mass spectrometry to measure protein concentration, protein half-life, cell proliferation, and ribosomal biogenesis in a single sample of murine articular cartilage. We hypothesized that a 60-d labeling period would capture age-related declines in cartilage matrix protein content, protein synthesis rates, and cellular proliferation. Knee cartilage was harvested to the subchondral bone from 25- to 90-wk-old female C57BL/6J mice treated with deuterium oxide for 15, 30, 45, and 60 d. We measured protein concentration and half-lives using targeted high resolution accurate mass spectrometry and d2ome data processing software. Deuterium enrichment was quantified in isolated DNA and RNA to measure cell proliferation and ribosomal biogenesis, respectively. Most collagen isoforms were less abundant in aged animals, with negligible collagen synthesis at either age. In contrast, age altered the concentration and half-lives of many proteoglycans and other matrix proteins, including several with greater concentration and half-lives in older mice such as proteoglycan 4, clusterin, and fibronectin-1. Cellular proteins were less abundant in older animals, consistent with reduced cellularity. Nevertheless, deuterium was maximally incorporated into 60% of DNA and RNA by 15 d of labeling in both age groups, suggesting the presence of two large pools of either rapidly (<15 d) or slowly (>60 d) proliferating cells. Our findings indicate that age-associated changes in cartilage matrix protein content and synthesis occur without detectable changes in the relative number of proliferating cells. Graphical Abstract: